Efect of Gamma 60Co Irradiation on The Growth, Lipid Content and Fatty Acid Composition of Botryococcus sp. Microalgae - Ermavitalini, Dini; Yuliansari, Niki; Prasetyo, Endry Nugroho; Saputro, Triono Bagus (Biosaintifika: Journal of Biology & Biology Education, 2017)
Botryococcus sp. is one of microalgae species that has a high lipid content as much as 75% of their dry weight. But, lipid production by microalgae is regulated by their environmental condition (pH, light, temperature, nutrition, etc). Mutagenesis induced by Gamma 60Co irradiation can be utilized to alter the Botryococcus sp. genetic to get microalgae mutant strain that can produce a higher lipid content than the wild strain. Botryococcus sp. was irradiated with different doses of gamma ray of 60Co (0, 2, 4, 6, and 10 Gy), and the effect on the growth, lipid content, and fatty acid composition of microalgae were observed. Research design used is random complete (RAL) with 95 % confident level for quantitive analysis based on the biomass and lipid contents. More over fatty acid composition was analyzed by Gas Cromatography-Mass Spectrometry (GC-MS). Results showed that Gamma irradiated gave an effect on growth and lipid content of Botryococcus sp. But between the control treatment (0 Gy) with microalgae irradiated dose of 2 Gy, 4 Gy and 6 Gy were not significantly different. Whereas between the control with 10 Gy irradiated was significantly different. The highest biomassa and lipid content are found in 10 Gy irradiated microalgae with 0.833 gram biomass and 41% lipid content. Fatty acid profile of Botryococcus sp. control has 6 fatty acids while 10 Gy irradiated microalgae has 12 fatty acids, with the long-chain fatty acids increased, whereas short-chain fatty acids decreased.